2009
DOI: 10.5547/issn0195-6574-ej-vol30-nosi2-7
|View full text |Cite
|
Sign up to set email alerts
|

Neoclassical Growth, Environment and Technological Change: the Environmental Kuznets Curve

Abstract: This paper investigates socially optimal patterns of economic growth and environmental quality in a neoclassical growth model with endogenous technological progress. In the model, environmental quality has a positive effect not only on utility but also on production. Moreover, cleaner technologies can be used in the economy if a part of the output is used in environmentally oriented R&D. In this framework, if the initial level of capital is low, then the shadow price of a cleaner technology is low in relation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…A visual description of the simulation model can be seen in Figure 1, and the whole model can be found in Appendix 5. According to the chosen parameters from the related literature (Raurich & Sorolla, 2014), (Rubio & Garcia, 2009) that allows us to simulate long-run economic growth and capital stock, we have obtained unstable increasing dynamics as in Figure 2 (Appendix 3). for consumption and capital stocks.…”
Section: Simulations and Resultsmentioning
confidence: 99%
“…A visual description of the simulation model can be seen in Figure 1, and the whole model can be found in Appendix 5. According to the chosen parameters from the related literature (Raurich & Sorolla, 2014), (Rubio & Garcia, 2009) that allows us to simulate long-run economic growth and capital stock, we have obtained unstable increasing dynamics as in Figure 2 (Appendix 3). for consumption and capital stocks.…”
Section: Simulations and Resultsmentioning
confidence: 99%
“…In this respect, our study is closely related to several works analyzing the relationship between economic growth, technological change, and the environment, for example, Selden and Song (1995), Stokey (1998). Bovenberg and Smulders (1995), Grimaud (1999), Reis (2001, Jones and Manuelli (2001), Cassou and Hamilton (2004), Ricci (2007), Cunha-e-sá and Reis (2007), and Rubio et al (2010).…”
Section: Introductionmentioning
confidence: 85%
“…(Tamazian et al, 2009) found evidence of an adverse association between financial development and carbon dioxide emissions. However, if new technologies are successful, the economy can grow balanced while improving environmental quality, as demonstrated by a turning point in this curve (Rubio et al, 2009). In 11 European economies in the post-transition era, a study (Bayar et al, 2020) examined the relationship and discovered a negative correlation between financial development and environmental degradation.…”
Section: Literature Review a Review On The Relationship Between Finan...mentioning
confidence: 99%